1995
DOI: 10.1017/s0022215100131688
|View full text |Cite
|
Sign up to set email alerts
|

Tympanosclerosis and mini grommets: the relevance of grommet design

Abstract: Fifty children with otitis media with effusion undergoing grommet insertion had into one ear a Minititanium grommet inserted and into the other ear a Mini-teflon grommet. Post-operative follow-up until after extrusion of the grommets demonstrated only a small difference between the extrusion times of the two grommets (a significant difference of 41 days) and no difference in the degree of tympanosclerosis seen with each grommet. We propose that the mass of a grommet appears to play less of a role than has prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…7 It appears that in OME ventilation tubes do not protect the ears against the long-term development of attic retraction or cholesteatoma, and there is no long-term audiological bene t. [3][4][5]7 On the contrary the insertion of ventilation tubes can itself cause complications such as tympanosclerosis, otorrhoea and persistent perforation, the extent of which depend on the particular design and duration of the ventilation tube. [8][9][10][11] In our survey ve per cent of otolaryngologists in group B gave repeated infection caused by ventilation tubes to be a reason for prescribing hearing aids. If ventilation tubes cannot prevent middle-ear complications, but can cause additional problems, why should ventilation tubes be re-inserted if OME recurs after the initial insertion of the ventilation tube along with surgical attention to possible predisposing factors such as adenoidectomy?…”
Section: Discussionmentioning
confidence: 70%
“…7 It appears that in OME ventilation tubes do not protect the ears against the long-term development of attic retraction or cholesteatoma, and there is no long-term audiological bene t. [3][4][5]7 On the contrary the insertion of ventilation tubes can itself cause complications such as tympanosclerosis, otorrhoea and persistent perforation, the extent of which depend on the particular design and duration of the ventilation tube. [8][9][10][11] In our survey ve per cent of otolaryngologists in group B gave repeated infection caused by ventilation tubes to be a reason for prescribing hearing aids. If ventilation tubes cannot prevent middle-ear complications, but can cause additional problems, why should ventilation tubes be re-inserted if OME recurs after the initial insertion of the ventilation tube along with surgical attention to possible predisposing factors such as adenoidectomy?…”
Section: Discussionmentioning
confidence: 70%
“…The duration in situ of the DT is defined as the time elapsed from insertion of the tube until the first follow‐up examination that showed extrusion of the tube. 4 Duration in situ is shown in Figure 2. Median duration in situ in the present study was 17 months (range, 1.5–36 mo).…”
Section: Resultsmentioning
confidence: 99%
“…Comparing titanium and Teflon grommets of identical dimensions, Dingle et al . 5 found that retention times were, on average, 41 days greater for the titanium grommets. Hussain 6 also found very significant difference in extrusion rates for Shah ventilation tube (mean of 13.03 months) compared to the Shepard design (mean of 10.39 months) at 8‐month assessment.…”
mentioning
confidence: 92%